2005
DOI: 10.1063/1.1988310
|View full text |Cite
|
Sign up to set email alerts
|

One-photon mass-analyzed threshold ionization spectroscopy of 2-chloropropene (2-C3H5Cl) and its vibrational assignment based on the density-functional theory calculations

Abstract: Articles you may be interested inOne-photon mass-analyzed threshold ionization (MATI) spectroscopy of pyridine: Determination of accurate ionization energy and cationic structure One-photon mass-analyzed threshold ionization spectroscopy of C H 2 Br I : Extensive bending progression, reduced steric effect, and spin-orbit effect in the cation J. Chem. Phys. 123, 024310 (2005); 10.1063/1.1954770 Vibrational assignment and Franck-Condon analysis of the mass-analyzed threshold ionization (MATI) spectrum of CH 2 Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The BMK/6-311++G(3df,3pd) optimized structure is shown in the Figure . Previous reported values for the 2-chloropropene geometrical parameters at MP2/6-311G(d,p) and B3LYP/6-31G(d) levels from Parsons et al, B3LYP/6-311++G(3df,3pd) from Bae et al, and B3LYP/6-311++G(d,p) from Chang et al are in good agreement with the present results.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The BMK/6-311++G(3df,3pd) optimized structure is shown in the Figure . Previous reported values for the 2-chloropropene geometrical parameters at MP2/6-311G(d,p) and B3LYP/6-31G(d) levels from Parsons et al, B3LYP/6-311++G(3df,3pd) from Bae et al, and B3LYP/6-311++G(d,p) from Chang et al are in good agreement with the present results.…”
Section: Resultssupporting
confidence: 93%
“…All values are in good agreement with previous theoretical results. 6,30,31 In addition, mode assignments obtained from the animation of the normal modes and by comparison with species containing similar chemical groups, are included in Tables 2 and B (Supporting Information). Certainly, some of the modes are strongly coupled, and therefore, only approximate assignments are given.…”
Section: Resultsmentioning
confidence: 99%
“…As a prototype of aliphatic halides, allyl chloride has attracted a great deal of interest due to its complex photodissociation dynamics [1][2][3][4][5][6][7][8][9][10][11][12][13] . The radiation of a UV photon possibly leads to C-Cl bond breaking and/or HCl elimination.…”
Section: Introductionmentioning
confidence: 99%
“…Both groups found that at least two channels are involved in the dissociation. As for the ionization dynamics, important constants, such as the accurate ionization potential, were also measured 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] The questions concerning the relative stability of the eclipsed and staggered conformations of cations containing CH 3 -CH=X functionalities can now be answered experimentally. For instance, Kim and his co-workers 28,29 have exploited mass-analyzed thresholdionization spectroscopy to study the methyl-torsional motion in CH 3 -CX=CH + 2 (X=Cl, Br) and found that the eclipsed form [ Fig. 1(a)] is favored both in the neutral and the cation, but that the barrier is very strongly reduced (to ∼50-100 cm −1 ) in the cations compared to the neutrals (∼1000 cm −1 ).…”
Section: Introductionmentioning
confidence: 99%